Trends in hospitalization for urinary tract infection in the paediatric age group in the 2000-2015 period in Spain - Jesús Redondo Sánchez; Alberto Manuel Domínguez Lázaro; Ricardo Rodríguez Barrientos; Jaime Barrio Cortes; Andrea Seoane Sanz; Juan Bravo Acuna; Isabel del Cura-González (Elsevier, 2023)
Objective: To analyse the trends in hospital admissions related to urinary tract infection among children aged 0-14 years in Spain in the 2000-2015 period. Methods: We conducted a retrospective observational study using the minimum basic hospital discharge dataset system of Spain, which applies the International Classification of Diseases, version 9 (ICD-9) coding system. We included every hospitalisation due to cystitis, pyelonephritis and unspecified UTI among children aged less than 15 years. We collected data on patient sex and age, type of discharge, main diagnosis, comorbidities, length of stay and overall cost. We calculated crude hospitalization rates per 1000 inhabitants aged less than 15 years and performed a joinpoint regression analysis to identify temporal trends. Results: In the 2000-2015 period, there were 124 696 hospitalizations in children under 15 years. Of these patients, 72.97% were aged 0-1 year and 60.12% had a diagnosis of unspecified UTI, 39.27% of pyelonephritis, and 0.52% of cystitis. The crude rate of hospitalization due to UTI ranged from 1.24 in year 2000 to 0.98 in 2015. The rate of hospitalization was higher in female versus male patients. The joinpoint analysis found a decreasing trend in the rate of hospitalization due to UTI, with an average annual percent change (AAPC) of −1.5% (95% confidence interval [CI], −2.4 a −0.6). The largest decreases occurred in female patients (AAPC, −1.8; 95% CI, −2.5 a −1.0) and children aged 7-10 years (AAPC − 5.9; 95% CI, −6.7 a −5.2). Conclusions: The rate of hospitalization related to UTI in Spain in patients aged up to 14 years decreased during the 2000-2015 period. The highest hospitalization rates occurred in female patients and in the 0-to-1 year age group. Resumen: Objetivo: Analizar las tendencias en la hospitalización por infección del tracto urinario (ITU) en menores de 0−14 años en España en el período 2000-2015. Métodos: Estudio retrospectivo observacional realizado por medio del conjunto mínimo básico de datos (CMBD) hospitalario con códigos de la Clasificación Internacional de Enfermedades (CIE-9). Se incluyeron todos los ingresos por cistitis, pielonefritis e ITU de localización no especificada en niños menores de 15 años. Se recogieron datos sobre el sexo, edad, tipo de alta, diagnóstico principal, comorbilidades, estancia hospitalaria y coste total. Se calcularon tasas crudas de hospitalización por 1000 habitantes menores de 15 años y se llevó a cabo un análisis de regresión segmentada para identificar tendencias temporales. Resultados: En el período 2000-2015, hubo 124 696 ingresos en niños menores de 15 años. De este total, el 72,97% tenían de 0 a 1 año y el 60,12% recibió un diagnóstico de ITU no especificada, el 39,27% de pielonefritis, y el 0,52% de cistitis. La tasa cruda de hospitalización por ITU osciló entre 1,24 en 2000 y 0,98 en 2015. La tasa de hospitalización por ITU fue mayor en niñas que en niños. El análisis de regresión segmentada mostró una tendencia decreciente en la tasa de hospitalización por ITU, con un porcentaje de cambio anual medio (PCAM) en la −1,5% (IC 95%: −2,4 a −0,6). Los cambios observados fueron mayores en niñas (PCAM − 1,8; IC 95%: −2,5 a −1,0) y en el grupo de 7 a 10 años (PCAM − 5,9; IC 95%: −6,7 a −5,2). Conclusiones: La tasa de hospitalización asociada a infección urinaria en pacientes menores de 15 años en España descendió durante el período 2000-2015. Las mayores tasas se dieron en niñas y en menores de 2 años.